2021
DOI: 10.3390/ijms22126247
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Adhesion of B-Lymphocytes to Specific Microenvironments in Mantle Cell Lymphoma: Interplay between Signaling Pathways and the Epigenetic Landscape

Abstract: Lymphocyte migration to and sequestration in specific microenvironments plays a crucial role in their differentiation and survival. Lymphocyte trafficking and homing are tightly regulated by signaling pathways and is mediated by cytokines, chemokines, cytokine/chemokine receptors and adhesion molecules. The production of cytokines and chemokines is largely controlled by transcription factors in the context of a specific epigenetic landscape. These regulatory factors are strongly interconnected, and they influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 157 publications
(206 reference statements)
0
5
0
Order By: Relevance
“…Although our understanding of microenvironment-mediated tumor cell survival and drug resistance has improved, the role of epigenetic mechanisms, especially histone modifications, in this process remains largely unknown [43]. Here, we demonstrate that signals from the tumor microenvironment induce upregulation of NF-κB genes in MCL cells by modifying their histone modification patterns.…”
Section: Introductionmentioning
confidence: 78%
“…Although our understanding of microenvironment-mediated tumor cell survival and drug resistance has improved, the role of epigenetic mechanisms, especially histone modifications, in this process remains largely unknown [43]. Here, we demonstrate that signals from the tumor microenvironment induce upregulation of NF-κB genes in MCL cells by modifying their histone modification patterns.…”
Section: Introductionmentioning
confidence: 78%
“…Chemokines and their receptors play pivotal roles in the progression of various cancers [18]. Studies in B-cell malignancies have revealed subtype-specific patterns of chemokine receptor expression, underscoring their crucial function in the dissemination of malignant B-cells, leading to the formation of monoclonal B-cells and tumor transformation [19,20]. Specifically, in DLBCL, research has highlighted the importance of chemokine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…MCL is characterized by the presence of the chromosomal translocation t(11;14) (q13;q32), considered as the genetic hallmark and one of the primary oncogenic events [21,22]. However, this event is not sufficient to confer the full lymphoma phenotype.…”
Section: The Biology Of Mantle Cell Lymphoma's Tumor Microenvironmentmentioning
confidence: 99%
“…MCL cell survival relies on BCR-mediated signaling and NF-kB pathways [31,32]. Several studies assessed the role of the TME interactions with the tumor B cell in this context, and subsequently the impact of BTK inhibitors [21,29,32]. Indeed, it is now well known that selective inhibition of BTK (or PI3Kdelta) within the BCR (or CXCR4) pathways leads to peripheral lymphocytosis by disrupting the interaction between the TME and tumor B cell and their homing [8,17,33,34].…”
Section: Bcr Activation In the Lymph Nodes Versus Peripheral Blood Mc...mentioning
confidence: 99%